DIVERSITY OF BATS IN HALABAN MONITORING POST AREA, SEI BETUNG, GUNUNG LEUSER NATIONAL PARK - Ardhina, Mahdiyyah; Berliani, Kaniwa; Tanjung, Masitta (Forestry Study Program University Of Mataram, 2024)
Halaban Monitoring Post, Sei Betung Resort, Gunung Leuser National Park is a rehabilitated forest restoration location since 2017 after previously being diversified from oil palm land. The location has currently become a habitat for various types of animals, including bats. The identification of bat species at the Halaban Monitoring Post is conducted to assess the presence of fauna, with important ecological roles in pollination. Identification was conducted using mist nets installed at five observation points. Our observations showed that 87 individuals of Microchiroptera family bats were found, belonging to 4 species: Cynopterus brachyotis (38 individuals), Cynopterus minutus (15 individuals), Glischropus tylopus (1 individual), Hipposideros cervinus (33 individuals). Further analysis showed Shannon-Wiener diversity index ranges from 0.0 to 0.94 and Margalef species richness index ranges from 0.0 to 0.69. Bat abundance tends to be evenly distributed with an evenness index of 0.0 to 1.35. There is a dominant species at one of the locations with a dominance index value of 0.85.